2015
DOI: 10.1016/j.joca.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical induction, histological evaluation, and MRI identification of cartilage necrosis in the distal femur in goats to model early lesions of osteochondrosis

Abstract: Objective Identify and interrupt the vascular supply to portions of the distal femoral articularepiphyseal cartilage complex (AECC) in goat kids to induce cartilage necrosis, characteristic of early lesions of osteochondrosis; then utilize MRI to identify necrotic areas of cartilage. Design Distal femora were perfused and cleared in goat kids of various ages to visualize the vascular supply to the distal femoral AECC. Vessels located on the axial aspect of the medial femoral condyle and on the abaxial side o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…First and foremost, limited availability of human cadaveric specimen forced us to draw our conclusions from a low number of observations. Previous studies in pigs 25 , horses 14 , and goats 19 , however, have indicated that the vascular supply to epiphyseal cartilage is highly predictable within a species at a given site and age. This limitation also prevented us from more closely matching the ages of pigs, goats, and humans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First and foremost, limited availability of human cadaveric specimen forced us to draw our conclusions from a low number of observations. Previous studies in pigs 25 , horses 14 , and goats 19 , however, have indicated that the vascular supply to epiphyseal cartilage is highly predictable within a species at a given site and age. This limitation also prevented us from more closely matching the ages of pigs, goats, and humans.…”
Section: Discussionmentioning
confidence: 97%
“…Given the large secondary center of ossification that was already present in the 1-day-old goat, it is likely that this transition occurs in goats prior to birth. In fact, this unique blood supply is likely to contribute to the goats’ lack of susceptibility for developing clinically apparent OCD even after surgical interruption of the vascular supply to the epiphyseal cartilage 19 , a procedure known to trigger the development of OCD like lesions in horses 14 . The shared predilection site of OC/OCD along with a nearly identical vascular architecture in pigs and humans provides an intriguing argument for utilizing pigs as a naturally occurring animal model of human OCD.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare the results of different studies when different sets of diagnostic criteria are used. In Table 2, we have summarized the progression of lesions following experimental vascular transection because the fact that progression was so similar suggests that it may be valid to use a single set of diagnostic criteria in several species 15,78,110,130 The experimental studies strongly indicate what the histological criteria could be, and there are also studies available that indicate how the histological criteria listed in Table 2 correlate with changes in diagnostic imaging modalities that can be used in live animals such as radiography, 79 CT, 82 and MRI. 110 …”
Section: What Is the Relationship Between The Studies Of Ischemic Chomentioning
confidence: 99%
“…Frontal slice, plain SWI MRI scan, reprinted with permission from Toth et al 111 by ex vivo MRI of the distal femur in goats. 110 Goats were chosen because they have not been reported to develop spontaneous osteochondrosis. Femurs were first imaged using a 3-dimensional gradient recalled echo sequence to identify the site of vessel transection.…”
mentioning
confidence: 99%
See 1 more Smart Citation